2022
DOI: 10.1021/acs.inorgchem.2c01818
|View full text |Cite
|
Sign up to set email alerts
|

[Fe2S2–Agx]-Hydrogenase Active-Site-Containing Coordination Polymers and Their Photocatalytic H2 Evolution Reaction Properties

Abstract: Three [Fe 2 S 2 −Ag x ]-hydrogenase active-site-containing coordination polymers (CPs), {[Fe 2were obtained by a direct synthesis method from ligands [FeFe](4-cpmt) 2 (CO) 6 [L1; 4-cpmt = (4-cyanophenyl)methanethiolate] and [FeFe](3-cpmt) 2 (CO) 6 [L2; 3-cpmt = (3-cyanophenyl)methanethiolate] with silver salts. 1− 3 represent the first examples of [FeFe]-hydrogenase-based CPs. It was worth noting that the Ag−S bonding between the Ag centers and S atoms of a [Fe 2 S 2 ] cluster produced a novel [Fe 2 S 2 −Ag x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…91,113,114 3.1 Photocatalytic H 2 evolution Hydrogen generation through photocatalytic reactions is quite attractive. Extensive efforts and impressive achievements have been reported by using MOF-based photocatalysts such as pristine MOFs, [115][116][117][118][119] hybrid MOFs with guest species like metal nanoparticles, 55,93,96,[120][121][122][123][124][125] metal suldes, 51,52,126-128 metal oxides, 54,[129][130][131][132] MXenes, 133 g-C 3 N 4 , 134,135 and MOF derivatives. 136,137 Recently, Ti 8 Zr 2 O 12 (COO) 16 clusters in bimetallic TiZr MOFs involving Ti 4+ and Zr 4+ ions were designed and prepared for the generation of hydrogen under light irradiation.…”
Section: Photocatalysis Based On Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…91,113,114 3.1 Photocatalytic H 2 evolution Hydrogen generation through photocatalytic reactions is quite attractive. Extensive efforts and impressive achievements have been reported by using MOF-based photocatalysts such as pristine MOFs, [115][116][117][118][119] hybrid MOFs with guest species like metal nanoparticles, 55,93,96,[120][121][122][123][124][125] metal suldes, 51,52,126-128 metal oxides, 54,[129][130][131][132] MXenes, 133 g-C 3 N 4 , 134,135 and MOF derivatives. 136,137 Recently, Ti 8 Zr 2 O 12 (COO) 16 clusters in bimetallic TiZr MOFs involving Ti 4+ and Zr 4+ ions were designed and prepared for the generation of hydrogen under light irradiation.…”
Section: Photocatalysis Based On Mofsmentioning
confidence: 99%
“…Hydrogen generation through photocatalytic reactions is quite attractive. Extensive efforts and impressive achievements have been reported by using MOF-based photocatalysts such as pristine MOFs, 115–119 hybrid MOFs with guest species like metal nanoparticles, 55,93,96,120–125 metal sulfides, 51,52,126–128 metal oxides, 54,129–132 MXenes, 133 g-C 3 N 4 , 134,135 and MOF derivatives. 136,137…”
Section: Photocatalysis Based On Mofsmentioning
confidence: 99%
“…Functionalized coordination polymers (CPs) and metal–organic frameworks (MOFs) have been attracting much attention due to their promising applications in adsorption and separation, catalysis, photoluminescence, biomedicine, etc. Among them, CPs and MOFs functionalized with [FeFe]-hydrogenase active sites have exhibited superior performance in photocatalytic H 2 evolution. However, the synthesis of [FeFe]-hydrogenase functionalized CPs or MOFs from [Fe 2 S 2 ]-containing ligands is still a big challenge due to the deficiencies of the ligand itself in thermal and chemical stability. In our last work, we brought forward a solution (i, rapid reaction with metals; ii, using nonprotonic solvents) to this problem and successfully obtained several stable [Fe 2 S 2 ] cluster-containing CPs . In the continuous research of this project, the coordination orientation of terminal −CN groups was changed by adopting a −CN group at the ortho -position of the substituted phenyl ring and the coordination environment of [Fe 2 S 2 ] cluster active sites were modified by using PPh 3 to replace CO. Then, the variation of geometric and electronic structures of the ligand would probably have an effect on the resulting polymeric structures and catalytic properties.…”
mentioning
confidence: 99%
“…In our last work, we brought forward a solution (i, rapid reaction with metals; ii, using nonprotonic solvents) to this problem and successfully obtained several stable [Fe 2 S 2 ] cluster-containing CPs. 14 In the continuous research of this project, the coordination orientation of terminal −CN groups was changed by adopting a −CN group at the ortho-position of the substituted phenyl ring and the coordination environment of [Fe 2 S 2 ] cluster active sites were modified by using PPh 3 to replace CO. Then, the variation of geometric and electronic structures of the ligand would probably have an effect on the resulting polymeric structures and catalytic properties. In this work, two new chelating ligands [FeFe](2-cpmt) 2 (CO) 6 (L1, 2-cpmt = (2-cyanophenyl)methanethiolate)) and [FeFe](2cpmt) 2 (CO) 5 (PPh 3 ) (L2) (Figure 1) were synthesized and their self-assembly reactions with Ag + produced four new Single-crystal analysis showed that [FeFe]-hydrogenase active sites were incorporated into the polymeric and supramolecular structures (Figure 2).…”
mentioning
confidence: 99%
“…The second reduction potential is −1.74 V, which is assigned to the reduction process of [Fe 0 Fe I ] to [Fe 0 Fe 0 ]. The electrochemical behavior of C1 is similar to that of catalyst C2 . By comparison, the first reduction potentials of C1 + 1, C1 + 2, C1 + 3, C1 + 4 , and C1 + 5 (−0.97, −0.86, −0.98, −0.94, and −0.78 V, respectively) all shifted to more positive potentials to some extent compared with that of C1 , thereby showing the occurrence of electron transfer from the MOFs to catalyst C1 .…”
mentioning
confidence: 99%